2005
DOI: 10.1111/j.1349-7006.2005.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cys‐603 in dimer/oligomer formation of the breast cancer resistance protein BCRP/ABCG2

Abstract: Breast cancer resistance protein (BCRP/ABCG2) is a half-molecule ATP-binding cassette transporter that we have previously suggested might function as a homodimer, bridged by disulfide bonds. In the present study, we carried out cysteine-scanning mutagenesis, substituting Ser for Cys, and established 12 PA317 transfectants expressing BCRP mutants with possible disruptions to their S-S bonds. Western blot analysis of BCRP from the wildtype transfectants (PA/WT) confirmed that the wild-type protein migrates as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 31 publications
2
73
2
Order By: Relevance
“…This possibility that protein-protein interactions are key for ABCG2 dimerization is a relatively new idea. Early work (24,42) showed that the simple withdrawal of reducing agent from the Laemmli buffer allowed the visualization of the ABCG2 dimer on a Western blot and proposed therefore that disulfide bonds between cysteines, specifically the C603 residue, was the critical residue in ABCG2 dimerization (43)(44)(45). However, more recent work has showed that the cysteines were not necessary for dimerization and that in vitro ABCG2 dimerized and trafficked without the need for disulfide bonds (43,(46)(47)(48), suggesting the importance of protein-protein interactions in ABCG2 dimerization.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility that protein-protein interactions are key for ABCG2 dimerization is a relatively new idea. Early work (24,42) showed that the simple withdrawal of reducing agent from the Laemmli buffer allowed the visualization of the ABCG2 dimer on a Western blot and proposed therefore that disulfide bonds between cysteines, specifically the C603 residue, was the critical residue in ABCG2 dimerization (43)(44)(45). However, more recent work has showed that the cysteines were not necessary for dimerization and that in vitro ABCG2 dimerized and trafficked without the need for disulfide bonds (43,(46)(47)(48), suggesting the importance of protein-protein interactions in ABCG2 dimerization.…”
Section: Discussionmentioning
confidence: 99%
“…However, Bhatia et al (2005) observed no effect of similar mutations on the trafficking or function of the mutant form of human ABCG2. Furthermore, Kage et al (2005) found that mutation of Cys603 had no effect on ABCG2 function. Thus, it is not yet clear whether formation of intermolecular disulfide bonds is responsible for ABCG2 dimerization and whether cysteine residues are important for its membrane targeting and function.…”
mentioning
confidence: 99%
“…Approximately 70 -80 residues long, ECL3 is large enough to constitute a full domain, although no specific role has been assigned to it. It contains three cysteine residues reported to be involved in both intermolecular (Cys 603 -Cys 603 ) and intramolecular (Cys 592 -Cys 608 ) disulfide bridges (31)(32)(33)(34). ECL3 also contains a conformational epitope recognized by the 5D3 monoclonal antibody (24), the interaction of which is prevented upon reduction of the intramolecular disulfide bridge Cys 603 -Cys 603 (35), making 5D3 a powerful conformation-sensing tool.…”
mentioning
confidence: 99%